The extent of decision-making criteria included in procurement legislation at Transnet port termianls (TPT). - Bhogal, Katherine (My University, 2022)
State Owned Entities (SOE’s), like Transnet Port Terminals, have been plagued with maladministration and poor governance within Procurement. In the last 20 years, SA government have procured goods and services from the private industry to an estimated value of between R400 to R500 billion per annum. Procurement is subject to Legislative requirements, that aim to reduce political influences, fraud and corruption and safeguard the decisions made to award contracts that result in government spending. The main aim of this exploratory study was to assess the extent of decision-making criteria included in Procurement Legislation at TPT, using the Bounded Rationality decision-making model. The thematic analysis research methodology was used to analyse the results of the research and indicated that there was no and (or) limited Legislation that govern and regulate decision-making within Procurement at TPT. There is an urgent need to update existing and develop new Legislation and Policies assist SOE’s, like TPT, adhere to sound governance principles that will improve decision-making for Procurement transactions and related expenditure.
A research report submitted in partial fulfilment of the requirements for the degree of Masters of Management (in the field of Governance and Management) to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022